MONTE-CARLO SIMULATION OF POLYAMPHOLYTE CHAINS - Desouza, A. R.; Degreve, L. (Gordon Breach Sci Publ Ltd, 1993)
Polyampholyte copolymers containing both positive and negative monomers regularly dispersed along the chain were studied. The Monte Carlo method was used to simulate chains with charged monomers interacting by screened Coulomb potential. The neutral polyampholyte chains collapse due to the attractive electrostatic interactions. The nonneutral chains are in extended conformations due to the repulsive polyelectrolyte effects that dominate the attractive polyampholyte interactions. The results are in good agreement with experiment.
Keywords: POLYAMPHOLYTE COPOLYMERS; MONTE CARLO SIMULATION; MACROMOLECULES; POLYAMPHOLYTE EFFECT